The Information Grid XML and database moving toward convergence. - Banerjee, Sandeepan
Two somewhat contrary sounding drivers fuel the emerging renaissance in enterprise data management-virtualization and convergence. Virtualization is a framework for dividing up the resources of an organization into multiple execution environments through the application of one or more technologies such as hardware clustering, software partitioning, application modularization, emulation, and so on. Convergence, on the other hand, tries to bring diverse information assets-databases, mail stores, documents-under unified management. The coming Information Grid unites these opposing drivers.